Color variation of electrophoretic styrene-acrylic paints under field and accelerated ultraviolet exposure. (15th February 2017) - Ecco, L.G.; Rossi, S.; Fedel, M.; Deflorian, F.
Abstract: Metals are mostly painted to improve corrosion protection of the coated item. Nevertheless, paints can be used to deliver visual aspects to them. Several investigations were conducted to comprehend color variation of paints as function of accelerated tests however, limited information is found concerning these variations versus field exposure. Thus, there is the interest to cover this lack of information and investigate color changes of waterborne paints versus field exposure. In this study colored styrene-acrylic painted steel panels were naturally aged in the alpine climate of Trento, northern of Italy. Color measurements were conducted according to the CIEL*a*b* standard. Gloss measurements and FT-IR spectroscopy assessed variations on the surface topography and chemical structure of the coated panels. It was observed that the changes in color of the colored paints were commanded by the interaction of ultraviolet radiation and they were dependent on the chemical nature of the color pigments. In addition, in the months with attenuated solar irradiance and predominance of TOWISO conditions, gloss reduction rates and L* of the coated panels have their evolution trend shifted. Upon accelerated UV.B ageing conducted in dry condition neither fluctuations on the L* nor attenuation on the gloss reduction rates were detected. Graphical abstract: Highlights: Color variation of pigmented coatings is sensible to RH and UV radiation. The time of wetness played a role on gloss and lightness. Different degradation mechanisms were observed in function of chemical nature of pigments. The accelerated UV ageing test discriminated the stability of the pigmented paints system.